Cultura corporativa e relacionamento interno: dando voz a funcionários e colaboradores - OLIVEIRA, Isabela Rodrigues de Figueiredo; FIGUEIREDO, Gabriela Rodrigues de (288, 2020)
Quanto mais as marcas souberem administrar e investir no bom relacionamento com seus funcionários, mais estes podem se sentir motivados e se empenharem em favor do crescimento do negócio. Posto desta forma, este estudo procura avaliar os conceitos de cultura corporativa e relacionamento interno, a fim de verificar como um investimento em funcionários e colaboradores pode ajudar não apenas na produção de bens e serviços, mas em elevar a reputação da marca e manter um relacionamento mais próximo aos públicos de interesse. Após evidenciar estes conceitos teóricos, apresenta um estudo exploratório, por meio de entrevistas a funcionários de uma empresa de construção civil de Araraquara/SP, a fim de avaliar como eles se sentem ao trabalhar na empresa e os benefícios de os gestores darem voz às suas opiniões. O que se nota, a partir deste estudo, é que quanto mais as empresas investirem nos funcionários, mais probabilidades de sucesso elas podem ter nos segmentos que atuam. Palavras-chave: Relacionamento interno. Cultura corporativa. Investimento em funcionários.

The more brands that know how to manage and invest in good relationships with their employees, the more they can feel motivated and strive for business growth. This study method, this study seeks to evaluate concepts of corporate culture and internal relationship, an end of verification as an investment in employees and collaborators can only help in the production of goods and services, but raise the reputation of the brand and maintain a closer relationship to stakeholders. After demonstrating these theoretical concepts, he presents an exploratory study, through interviews with employees of a civil construction company in Araraquara/SP, in order to evaluate how they feel working at the company and the benefits of the managers giving voiceThe more brands that know how to manage and invest in good relationships with their employees, the more they can feel motivated and strive for business growth. This study method, this study seeks to evaluate concepts of corporate culture and internal relationship, an end of verification as an investment in employees and collaborators can only help in the production of goods and services, but raise the reputation of the brand and maintain a closer relationship to stakeholders. After demonstrating these theoretical concepts, he presents an exploratory study, through interviews with employees of a civil construction company in Araraquara/SP, in order to evaluate how they feel working at the company and the benefits of the managers giving voiceto their opinions. If you notice, from this study, the more companies invest in employees, the more likely they are to succeed in the segments they operate. Keywords: Internal relationship. Corporative culture. Investment in employees.
Corporate culture and internal relationship: giving voice to employees and employees
Keywords: Marketing de relacionamento; Endomarketing; Cultura organizacional; Recursos humanos; Gestão e Negócios